Hemagglutinin amino acids related to receptor specificity could affect the protection efficacy of H5N1 and H7N9 avian influenza virus vaccines in mice. Issue 23 (17th May 2016) - Xu, Lili; Bao, Linlin; Lau, Siu-Ying; Wu, Wai-Lan; Yuan, Jing; Gu, Songzhi; Li, Fengdi; Lv, Qi; Xu, Yanfeng; Pushko, Peter; Chen, Honglin; Qin, Chuan
Abstract: The continuous and sporadic human transmission of highly pathogenic avian H5N1 and H7N9 influenza viruses illustrates the urgent need for efficacious vaccines. However, all tested vaccines for the H5N1 and H7N9 viruses appear to be poorly immunogenic in mammals. In this study, a series of vaccines was produced using reverse genetic techniques that possess HA and NA genes from the H5N1 virus in the genetic background of the high-yield strain A/PR/8/34 (H1N1). Meanwhile, a group of H7N9 VLP vaccines that contain HA from H7N9 and NA and M1 from A/PR/8/34 (H1N1) was also produced. The HA amino acids of both the H5N1 and H7N9 vaccines differed at residues 226 and 228, both of which are critical for receptor specificity for an avian or mammalian host. Mice received two doses (3 μg of HA each) of each vaccine and were challenged with lethal doses of wild type H5N1 or H7N9 viruses. The results showed that a recombinant H5N1 vaccine in which the HA amino acid G228 (avian specificity) was converted to S228 (mammalian specificity) resulted in higher HI titers, a lower viral titer in the lungs, and 100% protection in mice. However, a H7N9 VLP vaccine that contains L226 (mammalian specificity) and G228 (avian specificity) in HA showed better immunogenicity and protection efficacy in mice than VLP containing HA with either L226 + S228 or Q226 + S228. This observation indicated that specific HA residues could enhance a vaccine's protection efficacy and HA glycoproteins with both avian-type and human-type receptor specificities may produce better pandemic influenza vaccines for humans.